Mo-Si-B Alloy Formed by Optional Laser Melting Process - Zhengyou Guo; Renheng Han; Yanan Li; Yanqing Zhu; Bin Zhang; Hexin Zhang (International Journal of Analytical Chemistry)
In this research article, the molybdenum alloy was prepared by solid-solid doping, selecting pure Mo powder, amorphous Si powder, and B powder as the experimental raw materials for SLM molding. The density and mechanical properties of Mo-Si-B alloys prepared by SLM technology under different processes and compositions were explored, and at the same time, the microstructure of the obtained alloy was observed. The result shows that, with a laser power of 250 W, a scanning speed of 500 mm/s, and a scanning distance of 60 μm, the Mo4.5-Si2-B (at.%) alloy has the highest forming rate under the 120°parameters of the rotating scanning strategy, and the highest density is 94.22%.